An abnormality in sebaceous function in phenylketonuria. Issue 5948 (4th January 1975) - Burton, J L; Goolamali, S K; Shuster, S
Abstract : The sebum excretion rate has been found to be increased in female patients with phenylketonuria. This may be related to a depletion of midbrain dopamine and release of the sebotrophic hormone.